Dead of night - Baines, John V. 1909-1962; MacPhail, Angus 1903-1962; Redgrave, Michael 1908-1985; Withers, Googie 1917-2011 (Studio Canal, 2014)
"Ealing Studios' output from the 1940s and 1950s helped define what was arguably the golden age for British cinema. Starring Michael Redgrave, Googie Withers and Mervyn Johns, Dead of Night represented a departure for Ealing from the classic comedy mode and is instead a spooky psychological thriller made up of five chilling ghost stories. An architect visits a country house only to get trapped in a recurring nightmare involving tales of the occult told by fellow guests at the manor. A portmanteau work from four of Ealing's best directors, Dead of Night preyed masterfully on the country's post-war fears and paranoia."
"Ealing Studios - digitally restored by the BFI National Archive"--Container
Originally released as a motion picture in 1945
Feature aspect ratio: 1.37:1
Special features: Remembering Dead of night featurette (75 min), Restoration comparison, Stills gallery
Keywords: Horror films; Supernatural in motion pictures; Anthology films; Ventriloquism / Drama; Gamblers / Drama; Gamblers; Drama; Feature films; Fiction films; Thrillers (Motion pictures); Film; DVD-Video